Concepts and metrics of clinician attention: a scoping review protocol - Mark J Kissler; Katherine Kissler; Samuel C Porter; Angela Keniston; Katherine Jankousky; Marisha Burden (BMJ Open)
Introduction There is growing emphasis on the importance of both the cognitive and behavioural phenomenon of attention for clinicians engaged in patient care. Aspects of attention such as cognitive load, distraction and task switching have been studied in various settings with different methodologies. Using the protocol described here, we aim to systematically review the medical literature in order to map the concept of attention and to synthesise diverse concepts and methods under the broader category of research focused on ‘attention’.Methods and analysis Following the methodology described by the Joanna Briggs Institute and Arksey and O’Malley, our scoping review conducts an iterative search of Cumulative Index of Nursing and Allied Health Literature (CINAHL), Medline (PubMed) and EMBASE (Ovid). An initial limited search based on key concepts and terminology will generate relevant articles which in turn will be mined for additional keywords and index terms to guide a formal literature search. Our multidisciplinary team will extract data into a matrix, including a small random sample of the same studies (to ensure concordance), and present the results in a descriptive narrative format.Ethics and dissemination As a secondary analysis, our study does not require ethics approval, and we will ensure that included studies have appropriate approval. We anticipate results will identify diverse ways of conceptualising clinician attention and will provide a foundation for developing additional metrics and study methods to optimise attention in the clinical environment. We will disseminate results through journals and conferences and coordinate with colleagues doing work in adjacent fields.